Fluorescent Probes for the Supramolecular Interactions responsible for Binding of Polycyclic Aromatic Hydrocarbons to Hyperbranched Polyelectrolytes in Aqueous Media. Issue 3 (19th February 2021) - Ihde, Michael H.; Steelman, Ashley M.; Bonizzoni, Marco
Abstract: Cationic poly(amidoamine) (PAMAM) dendrimers are known as good supramolecular hosts for a variety of smaller water‐soluble guests. We expanded their binding scope to the uptake of very hydrophobic guests such as polycyclic aromatic hydrocarbons (PAH) in neutral aqueous solution. We used anthracene and pyrene as representatives of this family of hydrocarbons, and as capable fluorescent emitters to probe mode and location of interaction for these hydrocarbons with polycationic amine‐terminated PAMAM dendrimers. We used steady‐state and time‐resolved fluorescence emission spectroscopy, as well as fluorescence anisotropy measurements and selective quenching experiments, to establish the mode and location of these binding interactions, demonstrating that, although these probes may look relatively similar, their interaction with PAMAM dendrimers is nevertheless significantly different. The results presented here provide insight into the attractive forces at play in the uptake of featureless hydrophobic PAH guests by hydrophilic PAMAM dendrimer hosts, whose applications span practical challenges including chemical separations, analytical discrimination, solubility and bioavailability enhancement of hydrophobic compounds. Abstract :